Pengaruh Brand Image dan Lifestyle Terhadap Keputusan Pembelian Iphone Minat Beli Sebagai Variabel Intervening - Putri, Mina; Purbasari, Ratih Amanda; Muharromy, Elquina Pijar; Adji Pamungkas, Fathan Setya; Rahardhini, Marjam Desma (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to determine the effect of Brand Image and Lifestyle on Iphone Purchasing Decisions with Purchase Intention as an Intervening Variable. The method used in this research is quantitative method. The population in this study were students in Surakarta and the sample used in this study was 100. The data collection technique was carried out through a survey by distributing questionnaires. The data analysis technique uses SmartPLS software. The results showed that brand image has a positive and significant effect on purchasing decisions (β = 0.452; t = 3.903; p < 0.05), while lifestyle has a positive but insignificant effect (β = 0.159; t = 1.102; p> 0.05). Brand image also has a positive and significant effect on purchase intention (β = 0.404; t = 3.712; p < 0.05), as well as lifestyle (β = 0.404; t = 3.381; p < 0.05). The effect of brand image on purchasing decisions through purchase intention is significant (β = 0.113; t = 2.368; p < 0.05), while lifestyle through purchase intention is not significant (β = 0.113; t = 1.706; p > 0.05).